Dysfunctional Limbic Circuitry Underlying Freezing of Gait in Parkinson's Disease. (15th March 2018) - Gilat, Moran; Ehgoetz Martens, Kaylena A.; Miranda-Domínguez, Oscar; Arpan, Ishu; Shine, James M.; Mancini, Martina; Fair, Damien A.; Lewis, Simon J.G.; Horak, Fay B.
Highlights: FOG in PD is associated with increased resting-state connectivity between the amygdala and putamen. FOG in PD is associated with anti-coupling between the amygdala and frontoparietal network. These limbic alterations relate to FOG severity and a subjective fear of falling. Abstract: Freezing of gait (FOG) is a poorly understood symptom affecting many patients with Parkinson's disease (PD). Despite growing evidence of a behavioral link between anxiety, attention and FOG in PD, no research to date has investigated the neural mechanisms that might explain this relationship. The present study therefore examined resting-state MRI functional connectivity between the amygdala, striatum and frontoparietal attentional control network in PD patients with (freezers: n  = 19) and without FOG (non-freezers: n  = 21) in the dopaminergic 'off' state. Functional connectivity was subsequently correlated with an objective measure of FOG severity and a subjective scale of affective disorder within each group. Connectivity between the right amygdala and right putamen was significantly increased in freezers compared to non-freezers ( p  < 0.01). Furthermore, freezers showed increased anti-coupling between the frontoparietal network and left amygdala ( p  = 0.011), but reduced anti-coupling between this network and the right putamen ( p  = 0.027) as compared to non-freezers. Key functional connections between the amygdala, putamen and frontoparietal network were significantly associated with FOG severity and a fear of falling. This study provides the first evidence that dysfunctional fronto-striato-limbic processes may underpin the link between anxiety and FOG in PD. It is proposed that freezers have heightened striato-limbic load and reduced top-down attentional control at rest, which when further challenged by the parallel processing demands of walking may precipitate FOG.